Changes in Subcellular Distribution of n-Octanoyl or n-Decanoyl Ghrelin in Ghrelin-Producing Cells - Nishi, Yoshihiro; Mifune, Hiroharu; Yabuki, Akira; Tajiri, Yuji; Hirata, Rumiko; Tanaka, Eiichiro; Hosoda, Hiroshi; Kangawa, Kenji; Kojima, Masayasu (Frontiers in Endocrinology, 2013)
Background: The enzyme ghrelin O-acyltransferase (GOAT) catalyzes the acylation of ghrelin. The molecular form of GOAT, together with its reaction in vitro, has been reported previously. However, the sub-cellular processes governing the acylation of ghrelin remain to be elucidated. Methods: Double immunoelectron microscopy was used to examine changes in the relative proportions of secretory granules containing n-octanoyl ghrelin (C8-ghrelin) or n-decanoyl ghrelin (C10-ghrelin) in ghrelin-producing cells of mouse stomachs. The dynamics of C8-type (possessing C8-ghrelin exclusively), C10-type (possessing C10-ghrelin only) and mixed-type secretory granules (possessing both C8- and C10-ghrelin) were investigated after fasting for 48h or after two weeks’ feeding with chow containing glyceryl-tri-octanoate (C8-MCT) or glyceryl-tri-decanoate (C10-MCT). The dynamics of C8- or C10-ghrelin immunoreactivity (ir-C8- or ir-C10-ghrelin) within the mixed-type granules were also investigated. Results: Immunoelectron microscopic analysis revealed the co-existence of C8- and C10-ghrelin within the same secretory granules (mixed-type) in ghrelin-producing cells. Compared to control mice fed standard chow, the ratio of C10-type secretory granules increased significantly after ingestion of C10-MCT, whereas that of C8-type granules declined significantly under the same treatment. After ingestion of C8-MCT, the proportion of C8-type secretory granules increased significantly. Within the mixed-type granules the ratio of ir-C10-ghrelin increased significantly and that of ir-C8-ghrelin decreased significantly upon fasting. Conclusions: These findings confirmed that C10-ghrelin, another acyl-form of active ghrelin, is stored within the same secretory granules as C8-ghrelin, and suggested that the types of medium-chain acyl-molecules surrounding and available to the ghrelin-GOAT system may affect the physiological processes of ghrelin acylation.